Silver-Promoted Radical Cascade Aryldifluoromethylation/Cyclization of 2-Allyloxybenzaldehydes for the Synthesis of 3-Aryldifluoromethyl-Containing Chroman-4-one Derivatives - Qianqian Sun; Hongxiao Li; Xingyu Chen; Jian Hao; Hongmei Deng; Haizhen Jiang (Molecules, 2023)
A convenient silver-promoted radical cascade aryldifluoromethylation/cyclization of 2-allyloxybenzaldehydes has been developed. Experimental studies disclosed that the addition of aryldifluoromethyl radicals in situ produced from easily accessible gem-difluoroarylacetic acids to unactivated double bonds in 2-allyloxybenzaldehyde was an effective route to access a series of 3-aryldifluoromethyl-containing chroman-4-one derivatives in moderate to good yields under mild reaction conditions.